2020
DOI: 10.48084/etasr.3904
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Planar Tri-Band Notch UWB Antenna for X-Band, WLAN, and WiMAX

Abstract: In this work, a new ultra-wideband (UWB) antenna design with 2.08GHz to 12GHz impedance bandwidth and triple-band specifications is presented. The proposed antenna is formed by a truncated square patch, a partial ground plane, and a 50Ω microstrip line. Three different types of slots were used in order to induce notched bands. A C-shaped slot is etched on the radiating patch to obtain a notched band in 3.31-4.21GHz for WiMAX. An inverted U-shaped slot in the micro-strip line induces a second notched band in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
0
10
0
1
Order By: Relevance
“…Recently, it has become important to create a multinotch band antenna. To achieve WiMAX and WLAN dual band notches, an I‐shaped and C‐shaped stubs are embedded into the patch, 5 by using pin diodes WiMAX and WLAN notched bands that are obtained in Azim et al 6 The WiMAX/C, WLAN, and X‐band triple band notches are reported in earlier studies 7–9 . In Alotaibi and Alotaibi, 7 one C‐type, U‐type, and L‐type slits are used to notch interference due to WiMAX, WLAN, and X‐band.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, it has become important to create a multinotch band antenna. To achieve WiMAX and WLAN dual band notches, an I‐shaped and C‐shaped stubs are embedded into the patch, 5 by using pin diodes WiMAX and WLAN notched bands that are obtained in Azim et al 6 The WiMAX/C, WLAN, and X‐band triple band notches are reported in earlier studies 7–9 . In Alotaibi and Alotaibi, 7 one C‐type, U‐type, and L‐type slits are used to notch interference due to WiMAX, WLAN, and X‐band.…”
Section: Introductionmentioning
confidence: 94%
“…To achieve WiMAX and WLAN dual band notches, an I-shaped and C-shaped stubs are embedded into the patch, 5 by using pin diodes WiMAX and WLAN notched bands that are obtained in Azim et al 6 The WiMAX/C, WLAN, and X-band triple band notches are reported in earlier studies. [7][8][9] In Alotaibi and Alotaibi, 7 one Ctype, U-type, and L-type slits are used to notch interference due to WiMAX, WLAN, and X-band. A compact UWB antenna with a size of 24 Â 26.5 mm 2 covering an impedance bandwidth of 3.1-10.6 GHz, along with triple band notches at 3.3-3.7 GHz (WiMAX), 5-6 GHz (WLAN), and 7.1-7.76 GHz (X-band) is reported in Bharti et al 8 To notch triple bands 1.58-2.12 GHz, 2.24-2.68 GHz, and 3.08-3.78 GHz, an appropriate reverse bias voltage is applied to a partially grounded rectangular shaped UWB antenna is reported in Shome and Khan.…”
Section: Introductionmentioning
confidence: 99%
“…In general, a wearable antenna is stated to have high flexibility and competence in a system connected with the human body. Well-being, health, and lifestyle are the primary interests while implementing these systems [1][2][3][4][5]. Usually, wearable antenna desires for all modern applications must be lightweight, economical, almost maintenance-free, and do not require installation.…”
Section: Introductionmentioning
confidence: 99%
“…The use of body-worn electronic devices, such as smart glasses, watches, and textiles, has grown rapidly as a result of the increasing need for wireless communication. The main interests in the implementation of these systems are wellbeing, health, and lifestyle [2]. As a result, Wireless Body Area Networks (WBANs) have attracted considerable attention [3].…”
Section: Introductionmentioning
confidence: 99%